Axial and hoop ratcheting assessment in pressurized steel elbow pipes subjected to bending cycles. (February 2018) - Foroutan, M.; Ahmadzadeh, G.R.; Varvani-Farahani, A.
Abstract: The present study evaluates ratcheting response of pressurized elbow pipes made of three steel alloys of austenitic stainless steel, 1020 steel, and 304L stainless steel subjected to external bending under load-controlled conditions by means of the Ahmadzadeh-Varvani (A-V) hardening rule. The model enabled ratcheting assessment of elbows in different directions mainly due to parameters implemented in the dynamic recovery term. The internal variable b ¯ in the model calibrated the backstress evolution over stress cycles and along with Macaulay functions controlled non-proportionality, directionality, and plastic shakedown over ratcheting progress in elbow pipes. A finite element model was employed to evaluate stress components at various positions on the elbow midsection. Experimental ratcheting data measured by strain gauges at different elbow positions of crown, intrados, and extrados closely agreed with those of ratcheting strains predicted based on the A-V model. Graphical abstract: fx1 Highlights: Axial and hoop ratcheting strains of pressurized steel elbow pipes were evaluated. Finite element method was employed to analyse stresses at the midsection of elbow. Ratcheting was assessed based on the A-V hardening rule at various elbow positions. The A-V model due to its dynamic recovery terms accounted for loading directionality. Internal variable b ¯ of the A-V model calibrated backstress evolution over stress cycles.